ANALISIS PENGARUH PERCEIVED RISK, SOCIAL NORMS, USEFULNESS, DAN TRUST TERHADAP ADOPSI MOBILE BANKING DAN INTERNET BANKING - Irni Audini; Idrianita Anis (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2017)
The purpose of this study was to determine the influence of perceived risk, social norms, usefulness and trust towards the adoption of mobile banking and internet banking in Indonesia. Independent variables in this study were perceived risk, social norms, usefulness and trust. Dependent variables used were the adoption of mobile banking and internet banking. The control variables of this study were gender, age, education, profession and understanding of technology.The research used questionnaire for data collection. The respondents were active users of mobile banking services banking and internet banking. The sampling technique used was purposive sampling. This study uses regression analysis. The analytical tool used to test the hypothesis is SPSS 20.These results indicate that not all independent variables showed significant effects on the dependent variable. Perceived risk has a negative influence on the adoption of mobile banking and internet banking. Social norms and trust have a positive influence on the adoption of mobile banking and internet banking. Usefulness has no influence on the adoption of mobile banking and internet banking. The control variables of age proved to be a positive influence on the adoption of mobile banking and internet banking. However, other variables, namely gender, education, profession and understanding of the technology do not affect the adoption of mobile banking and internet banking.